Effect of glutens of different quality on dough characteristics and breadmaking performance - Marchetti, Lucas (2012)
Glutens of different quality were extracted from commercial flours of distinct breadmaking performance and employed as improvers at a level of 1 g/100 g. The same flours used as a source of gluten were employed for testing the gluten effect. Flours were characterized by farinographic and alveographic assays and their protein profile was determined by SDS-PAGE. Rheology of each dough without and with gluten addition was studied by empirical and fundamental assays. Breadmaking performance was evaluated by loaf volume measurements and crumb texture. Though protein content was similar for all flours (11 g/100 g), dough exhibited different breadmaking characteristics which could be related to a different gliadin/glutenin proportion and a different protein profile. The weakest flour lacked two glutenin subunits (83 and 64.5 kDa) and showed a lower number of bands of gliadins respect to the other ones. Adding any of the three types of gluten to the weakest flour resulted in an increase of farinographic stability. The medium and inferior quality flours showed an increase in dough elasticity when the strongest gluten was added. In breadmaking assays the medium quality flour and its mixtures with gluten showed the highest specific volumes.